Loss carryover provisions Measuring effects on tax symmetry and automatic stabilisation - Hanappi, Tibor (OECD Publishing, 2018)
Loss carryover provisions are an essential part of corporate tax systems. Economic theory suggests that perfect intertemporal loss offsets are a necessary condition for the neutrality of corporate taxation across investment projects with different risk profiles. However, in practice the tax treatment of losses does often not reach this standard, e.g., due to lack of inflation indexation or tax offset restrictions. Using detailed country-level information, this paper presents two tax policy indices capturing the effects of carryover provisions on tax symmetry and stabilisation across a total of 34 OECD and non-OECD countries. The tax symmetry index captures the effectiveness of carryover provisions, including carry-forwards and carry-backs, relative to full symmetry, while the stabilisation index captures the proportion of an adverse revenue shock on loss-making firms which is absorbed by the corporate tax system. The results show that only 18 countries provide unlimited carry-forwards and most countries do not index tax losses to inflation; only 9 countries provide carry-backs while 8 countries limit the amount of tax losses which can be offset in any given year. Cross-country comparison of the two indices suggests that these restrictions have significant impacts on tax symmetry and stabilisation. Perfect tax symmetry is not achieved by the majority of the included corporate tax systems thus implying possible tax-induced distortions towards less risky projects
Keywords: Taxation